Grotesque Realities in Adverse Worlds (Global Journal of Human-Social Science, 2022)
The grotesque realities have been present since the beginning of history; in this case, moving from the so-called cave art to the contemporary; the separation of the grotesque aesthetic in human creations is inevitable. This aesthetic is the reflection of what we do not want to be, of the fantastic, mythical, mystical, etc. In this article, we find concepts of grotesque aesthetics that derive and deform the canons, from an aesthetic of the beautiful and the socially established.
Keywords: aesthetic; grotesque; reality; everyday life; deformation; body